Identifying Genetic Variants in Adolescents With Oppositional Defiant Disorders and/or Conduct Disorders: A Brief Report. Issue 3 (16th September 2016) - Oruche, Ukamaka Marian; Ross, Sydney E.; Carpenter, Janet S.; Renbarger, Jamie
Abstract : PROBLEM: To add to diversity in our state biobank, we explored the feasibility of collecting genetic material from adolescents with oppositional defiant disorder (ODD) and/or conduct disorder (CD) and their family members. We also preliminarily explored genetic factors associated with ODD and/or CD by comparing participant data to 1000 Genome Project data on minor allele frequencies. METHODS: Adolescents with ODD and/or CD and family members provided saliva samples for genetic testing. We evaluated five single‐nucleotide polymorphisms (SNPs), respectively, in the dopamine receptor subtype D2, dopamine receptor subtype D3, dopamine beta‐hydroxylase, dopamine transporter gene SLC6A3, and alpha‐2‐adrenergic receptor genes. Fisher's exact tests were used to examine differences in minor allele frequencies for each SNP. FINDINGS: Thirty‐one viable samples were genotyped from 15 affected adolescents and 16 unaffected family members; the 60% consent rate reflected high feasibility. Compared with the 1000 Genome Project frequencies, affected adolescents had higher frequencies of the genetic variant in the dopamine receptor subtype D2 ( p = .05) and dopamine beta‐hydroxylase ( p = 0.03), but not of the other three SNPs examined. CONCLUSIONS: Collecting genetic materials from an ethnically diverse sample of affected adolescents and their families is feasible. We offer practical suggestions to strengthen the integrity of future research studies.